Inflammatory bowel disease and evaluation of pregnancy and fertility - Rui ZHU; Yun-Ling WEN; Ying-Lei MIAO (Yixue xinzhi zazhi)
Inflammatory bowel disease (IBD) is a chronic non-specific inflammatory bowel disease of unknown etiology, mainly including ulcerative colitis (UC) and Crohn's disease (CD). Recently, the inci-dence of IBD has been on the rise in China, and its peak age of onset overlaps with the reproductive age, so safe and effective evaluation of IBD patients' pregnancy and fertility is a challenge for clinicians. This paper summarizes the pregnancy and fertility related problems in IBD patients, in order to provide ref-erence for the treatment of IBD patients of childbearing age.